Serum vascular endothelial growth factor as a marker for tubal pregnancy - Cabar,Fábio Roberto (2022)
SUMMARY OBJECTIVE: The objective of this study was to evaluate whether a single measurement of vascular endothelial growth factor could distinguish between intrauterine pregnancy and ectopic pregnancy and to correlate the levels of vascular endothelial growth factor with serum levels of progesterone andβ-human chorionic gonadotropin in each subgroup. METHODS: Ninety patients with a positive human chorionic gonadotropin test and either abdominal pain or vaginal bleeding were selected; pregnancies were singletons, spontaneously conceived, 42–56 days of gestational age. All patients had a transvaginal ultrasound examination and were divided into three subgroups: abnormal intrauterine pregnancy, tubal pregnancy, and normal intrauterine pregnancy. Tubal pregnancies were surgically treated and histologically confirmed. Blood samples were collected for the determination of β-human chorionic gonadotropin, progesterone, and vascular endothelial growth factor and their concentrations were compared in each subgroup. Receiver operating characteristic curve was calculated by comparing the subgroup of tubal pregnancy to the other groups. A Fisher discriminant function analysis was performed. The level of significance was 5%. RESULTS: One-way analysis of variance revealed a significant correlation between the different subgroups and β-human chorionic gonadotropin, progesterone, and vascular endothelial growth factor serum levels (p<0.001). Vascular endothelial growth factor concentration was significantly higher for patients with tubal pregnancy than for other subgroups (p<0.05). β-Human chorionic gonadotropin and progesterone levels were higher in the subgroup with normal intrauterine pregnancies compared with the subgroups with tubal and abnormal intrauterine pregnancies (p<0.05). Serum vascular endothelial growth factor level >188.7 ng/mL predicted tubal pregnancy with 96.7% sensitivity, 95.0% specificity, 90.6% positive predictive value, and 98.3% negative predictive value. CONCLUSIONS: Serum vascular endothelial growth factor could be a marker in discriminating intrauterine pregnancy from tubal pregnancy; its levels are increased in women with ectopic pregnancy compared with women with normal and abnormal intrauterine pregnancies.